2015
DOI: 10.1038/ng.3215
|View full text |Cite
|
Sign up to set email alerts
|

The genomic and phenotypic diversity of Schizosaccharomyces pombe

Abstract: Author contributions DCJ coordinated all analyses, isolated DNA for sequencing, analysed and filtered SNP calls, conducted diversity analysis and GWAS and drafted the manuscript. CR produced phenotype data for growth on various solid media and growth rates in liquid media. AR conducted analysis of dating using mitochondrial data. DS conducted GWAS. MP analysed all phenotype data. TM identified LTR transposon insertions and analysed transposon insertion data. FXM conducted crosses for analysis of spore viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
366
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(382 citation statements)
references
References 61 publications
10
366
6
Order By: Relevance
“…This line shows the maximum cell length and calcofluor staining (a marker of incomplete cell division and filamentous growth) among 160 lines that were recently phenotyped (Jeffares et al 2015). However, no overt morphologic differences were observed between MA lines with and without mutations in this gene.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…This line shows the maximum cell length and calcofluor staining (a marker of incomplete cell division and filamentous growth) among 160 lines that were recently phenotyped (Jeffares et al 2015). However, no overt morphologic differences were observed between MA lines with and without mutations in this gene.…”
Section: Resultsmentioning
confidence: 88%
“…fewer than 3 kb in S. cerevisiae (Liti et al 2009), the same drop in S. pombe requires between 20 kb (Jeffares et al 2015) and 50 kb (data not shown). A possible explanation is that S. pombe undergoes less frequent outcrossing in the wild.…”
Section: Similarities and Differences Between Fission And Budding Yeastsmentioning
confidence: 79%
See 2 more Smart Citations
“…Indeed, Schizosaccharomyces has been described to be isolated from wines showing strong organoleptic and chemical deviations such as high levels of acetic acid, sulfidric acid, acetaldehyde, acetoin and ethyl acetate [12]. Due to the enormous variability in the genetic composition of any species such as S. pombe [18], recent selection processes have been performed in order to obtain proper strains for winemaking purposes [19,20]. The last studies regarding Schizosaccharomyces genus have demonstrated that it is possible to produce quality wines through the combination of wild Schizosaccharomyces strains with selected Saccharomyces strains or more recently through the use of selected Schizosaccharomyces strains that are able to perform by themselves a complete proper fermentation process, especially under very acidic conditions.…”
Section: Introductionmentioning
confidence: 99%